Necesidad de establecer el derecho a la muerte digna en la Constitución - Medrano Chamorro, Myrian Elizabeth (2016)
The Constitution issued in 2008, several horizons were deployed in different areas especially in relation to inalienable and fundamental rights for all persons within the national territory, which establishes a whole chapter to the rights of Ecuadorian citizens, guaranteed in the Constitution and in international instruments. However, I think recognize freely and voluntarily, the right to die with dignity, to patients with terminal diseases with irreversible diseases, incurable or brain death is not in the best health conditions in which the medicine is no longer able to have results positive. The proposal of the right to die with dignity is aimed at patients in the final stages of terminal stage of incurable disease, or brain dead, with the prior approval of the same patient or their relatives to the fourth degree of consanguinity or your spouse or partner in Free Union, if you lost your consciousness, the way to do so is through a living will, which rest on the patient's history, from the issuance of the document, which will be allowed to sidestep the suffering of these people. Dignified death is a way for these people to be at the expense of their health, obtain the right to decide freely on their health, in the sense of opposing the future application of treatments and medical procedures to prolong their life in the case of diagnosis terminal, incurable illness or irreversible brain dead, to avoid further lengthen the suffering and pain of the patient and his family. Consequence of the lack of legislative standard for a dignified death has taken place especially in private clinics, look at the patient as a source of money, and not as a human being, as to prolong his life with a series of technological equipment sophisticated medical , recharges the patient and his family the emotional and economic effects, the cost of providing equipment that keeps on life for the terminally ill. Is evidence that patients with terminal lacking a law that could qualify to meet their autonomy, and decide for the right to die diseases, no option but to prolong their suffering until the end of their existence left. To the extent that you can legislate, you need to open your eyes to new legal possibilities, seeking those patients the right to a dignified death without pain and with the conviction that every human being deserves to conclude the last stage of their lives with dignity. In response to this problem it is necessary to include in the Constitution of the Republic of Ecuador in Chapter V concerning the rights of freedom, a section for "Dignified Death", so that patients are guaranteed with terminal, irreversible diseases, incurable or brain dead, be recognized on a voluntary and autonomous right to die with dignity